TEACHERS COMPETENCIES PROFILE IN DIGITAL LEARNING ERA: PROFESSIONAL ENGAGEMENT AND SELECTING DIGITAL RESOURCES - Budi Wibawanta; Imanuel Adhitya Wulanata Chrismastianto; Billy Mumu (STKIP Melawi, 2021)
Abstract: Observing technological developments in the digital learning era with increasingly massive 21st-century skills approach in the education sector must be responded to with professional teacher competence. This study aims to analyze the extent to which the teacher's competencies in professional engagement and selecting digital sources in the teaching and learning process. The research methodology used was survey research to subject's teachers as many as 61 respondents located at Dian Harapan Karawaci School, Tangerang. Respondent data collection was carried out by filling in an online questionnaire using google form media which was analyzed qualitatively descriptively. The results showed that the three aspects of a teacher's competencies profile in the digital learning era have been achieved in a good category so that they can meet the criteria for teacher's competencies profile as expected. Even though it has reached the good category, there are two sub-aspects with supporting items that need further efforts to improve teacher competence through professional development or similar teacher training, namely DCPD-3 and DCPD-4.Keywords: Teacher, competencies, professional engagement, digital resources